ASSESSMENT OF CEMENT QUALITY AND ITS LINK TO BUILDING COLLAPSE IN LAFARGE CEMENT COMPANY, ASHAKA - A.U. SHELLENG; M. MIJINYAWA; M.I BAMMAMI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The sequential increase in building collapse in Nigeria has made it necessary to study the quality of cement that are available commercially in Nigeria. The assessment of some quality parameters of Lafarge Cement Company, Ashaka, Gombe state Nigeria was carried out in this research using a secondary data for 7 years (2009 to 2015). To ascertain whether the quality of cement produced by Ashaka cement company conform to the Nigerian Industrial Standard (NIS), the following tests as specified by Standard Organization of Nigeria, SON (NIS444- 1:2003) compressive strength, setting time, and soundness are considered as test parameters to ensure the quality of the cement. R package was used to construct the control charts for the study variables. Process Capability Analysis was also carried out to know whether the process was capable of producing conforming products that meets SON’s specification. It was discovered that Ashaka cement production was under statistical control and all the parameters tested met the required standard set by SON. It was also discovered that the controversy linking Ashaka cement quality to building collapse is misapplication of the cement product. It was recommended that SON should upgrade the quality of cement sold in Nigeria to 32.5, 42.5 and 52.5 brands and their quality and purpose should be clearly written on their packaged bags.